Reliability of field methods for estimating body fat. (3rd May 2013) - Loenneke, Jeremy P.; Barnes, Jeremy T.; Wilson, Jacob M.; Lowery, Ryan P.; Isaacs, Melissa N.; Pujol, Thomas J.
Summary: When health professionals measure the fitness levels of clients, body composition is usually estimated. In practice, the reliability of the measurement may be more important than the actual validity, as reliability determines how much change is needed to be considered meaningful. Therefore, the purpose of this study was to determine the reliability of two bioelectrical impedance analysis (BIA) devices (in athlete and non‐athlete mode) and compare that to 3‐site skinfold (SKF) readings. Twenty‐one college students attended the laboratory on two occasions and had their measurements taken in the following order: body mass, height, SKF, Tanita body fat‐350 (BF‐350) and Omron HBF‐306C. There were no significant pairwise differences between Visit 1 and Visit 2 for any of the estimates ( P >0·05). The Pearson product correlations ranged from r = 0·933 for HBF‐350 in the athlete mode (A) to r = 0·994 for SKF. The ICC's ranged from 0·93 for HBF‐350(A) to 0·992 for SKF, and the MD's ranged from 1·8% for SKF to 5·1% for BF‐350(A). The current study found that SKF and HBF‐306C(A) were the most reliable (<2%) methods of estimating BF%, with the other methods (BF‐350, BF‐350(A), HBF‐306C) producing minimal differences greater than 2%. In conclusion, the SKF method presented with the best reliability because of its low minimal difference, suggesting this method may be the best field method to track changes over time if you have an experienced tester. However, if technical error is a concern, the practitioner may use the HBF‐306C(A) because it had a minimal difference value comparable to SKF.